Pemikiran Sayyid Quthb dalam Pendidikan Etika Peserta Didik di Smpit Al-Mumtaz Pontianak - Fitriyanto, Andry Fitriyanto; Kurniawan, Syamsul Kurniawan; Rahman, Ummul Rahman (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2024)
This article contains a description of the reflection of Sayyid Qutb's thoughts in the ethics education of students at SMPIT Al-Mumtaz Pontianak. As the most influential figure in the Muslim Brotherhood organization, The derivation of Qutb's thought was firmly embedded in his patron organization such as the Kesatuan Aksi Mahasiswa Muslim Indonesia (KAMMI). SMPIT Al-Mumtaz is one of the places to continue the mission of this organization by their cadres. It’s more important to see how the thought of this figure's intersects with the perception of ethical education for students at the school. Indeed, ethics is a branch of philosophy that studies human behavior to determine whether an action is good or bad. However, in this research, student ethics refers more to the manners or morals that a student of science must have. The research method used was descriptive qualitative in the research object of the perceptions of SMPIT Al-Mumtaz Pontianak teachers regarding student ethics. By first explaining the concept of ethical education for students in Sayyid Qutb's view and then looking at its relevance in the perceptions of teachers at SMPIT Al Mumtaz Pontianak regarding student ethics which is used as a basis for carrying out their educational activities. This study concludes that; First, Sayyid Qutb divided two types of society, namely Islamic society which practices Islamic ethics in all aspects of its life, and jahiliyah (ignorance) society which does not practice it. This second type is the main cause of the decline of Muslims. For this reason, efforts are needed to return the situation to a more ideal direction with the focus of improving ethics in an Islamic education system. Among these foundations are being polite and patient in the learning process with teachers, being serious and ready to accept risks in seeking knowledge, straightening out intentions, and choosing a credible place of Islamic education; Second, there is relevance between the perception of SMPIT teacher Al Mumtaz and the ethical foundations of Sayyid Qutb's students, starting from the conception and practice of respect for teachers, seriousness in learning, straightness of intentions, and avoiding intellectual arrogance; Third, there are differences in perception in terms of choosing a place of education in an effort to form student ethics. Where the majority of respondents questioned the incompatibility of students' Islamic background with their choice of school. Only a small number of respondents did not mind it.